Presumptive Neonatal Multisystem Inflammatory Syndrome in Children Associated with Coronavirus Disease 2019 - Divekar, Abhay A.; Patamasucon, Pisespong; Benjamin, Joshua S. (American Journal of Perinatology, 2021)
Objective The study aimed to alert the neonatal community to the possibility of multisystem inflammatory syndrome in children (MIS-C) like disease in critically ill neonates born to mothers with coronavirus disease 2019 (COVID-19).Study Design Diagnosis of MIS-C like disease was pursued after echocardiography showed severely depressed ventricular function and pathological coronary artery dilation in the setting of medically refractory multisystem organ failure and maternal COVID-19 infection. The neonate did not respond to standard medical therapy, and there was no alternative disease that could explain the clinical course. High index of clinical suspicion coupled with low risk of intravenous immunoglobulin (IVIG) prompted us to pursue IVIG administration even though the neonate did not meet classic criteria for MIS-C.Result Following treatment with IVIG, there was rapid clinical improvement. Ventricular function improved within 15 hours and coronary artery dilation resolved in 8 days. There was no recurrence of disease during follow-up.Conclusion COVID-19 associated MIS-C like disease has not been well described in neonates. As typical features may be conspicuously absent, a high index of suspicion is warranted in critically ill neonates born to mothers with COVID-19. Echocardiography may provide critical diagnostic information and narrow the differential diagnosis.Key Points
Keywords: multisystem inflammatory syndrome in children; COVID-19; neonate; severe acute respiratory syndrome coronavirus 2; intravenous immunoglobulin